VL Sabji Matar 13: Early garden pea cultivar - Hedau, N K; Chaudhari, G V; Ram, Hanuman (Indian Horticulture, 2020)
‘VL Sabji Matar 13’ (Pisum sativum L. var. hortense) is new garden pea cultivar released for Agro-ecological Zone I (Uttarakhand) of India. The cultivar was developed by hybridization between VP 272 × Arkel followed by selection using pedigree method. Being early in maturity, therefore, it escapes powdery mildew. In addition, it also possesses resistance against white rot, wilt and leaf blight diseases under field conditions. It has less incidence of pests like pod borer under mid hills conditions. It has attractive green longer curved pods (high consumer liking), more seeds/pod and high shelling per cent. The average green pod yield is 11- 13 t/ha. It is suitable for cultivation under both organic and inorganic conditions.